Clenbuterol, salbutamol, and ractopamine in fresh meat products in Jilin province, China. Issue 1 (1st January 2019) - Xu, Chaojian; Gao, Haicheng; Pan, Nanzhu; Jiang, Mengmeng; Huang, Yi; Zhu, Ketong; Gong, Pingsheng; Lv, Shaowu
ABSTRACT: This study was designed to investigate clenbuterol, salbutamol, and ractopamine concentrations in fresh meat products. A total of 801 samples of ribs, loin, and internal organs of pigs, cattle, and lamb were collected from retail and wholesale markets in nine districts of Jilin Province, Northeast China. The three β-agonists were analyzed by LC-MS/MS. Results showed that 11.36% of the samples contained prohibited β-agonists. Detection rates of β-agonists decreased in the following order: Clenbuterol (6.37%) > Ractopamine (2.62%) > Salbutamol (2.37%). The β-agonists levels were higher for pork than for beef and lamb. The detection rate of meat products decreased in the following order: pork loin (28.72%) > pork ribs (24.72%) > pork internal organs (20.24%) > beef loin (6.67%) > beef internal organs (6.19%) > beef ribs (5.00%) > lamb internal organs (3.45%) > lamb ribs (3.41%) > lamb loin (3.26%). Only one β-agonists was detected per sample. On the surface of our research, the amount β-agonists of added to fresh meat products in Jilin Province of China is relatively safe.